Inhibition of Pseudomonas aeruginosa biofilm formation on copper-based thin foils. - Andrea Timoncini; Luca Lorenzetti; Raymond J Turner; Ashley McGibbon; Carla Martini; Elena Cofini; Elena Bernardi; Cristina Chiavari (PLoS ONE, 2024)
The development of Healthcare-Associated Infections (HAIs) represents an increasing threat to patient health. In this context, Pseudomonas aeruginosa is responsible for various HAIs, determining about 20% of the infections in hospitalized patients, which makes it one of the most effective pathogens due to its strong ability to form biofilms. Using Cu-based materials as foils on high-touch surfaces can help to prevent and mitigate P. aeruginosa contamination in biohazardous settings. However, the antibiofilm properties of Cu-based surfaces against P. aeruginosa may vary due to frequent touches combined with indoor environmental exposure. The main aim of this study is to investigate the impact of accelerated ageing, mimicking a high-touch frequency by cyclic exposure to artificial sweat solution as well as to temperature and relative humidity variations, on the efficacy of Cu-based thin foils against P. aeruginosa biofilms. Three Cu-based materials (rolled and annealed Phosphorous High-Conductivity (PHC) Cu, Cu15Zn brass, and Cu18Ni20Zn nickel silver) were evaluated. The ageing process enhanced the antibiofilm properties, due to an increment in Cu ion release: aged PHC Cu and Cu15Zn exhibited the highest Cu ion release and hence the highest biofilm inhibition (decrease in colony forming unit (CFU)) in comparison to their pristine counterpart, while aged Cu18Ni20Zn displayed the lowest biofilm formation reduction, despite showing the highest aesthetic and morphological stability. The Cu-based surface, which highlited the highest biofilm formation inhibition due to accelerated ageing, was Cu15Zn.